Michell Structures within L-Shaped Domains - Bołbotowski, Karol; Lewiński, Tomasz; Sokół, Tomasz (Computer Assisted Methods in Engineering and Science, 2020)
By recalling the main mathematical results concerning the theory of Michell structures, the present paper puts forward an interpretation of the selected numerical methods for constructing their approximants, that is, trusses with a large number of nodes. The efficiency of one of these methods: the ground structure method in its adaptive version is shown in the context of the L-shaped design domain problem. A large family of highly accurate truss approximants corresponding to the point loads acting at selected vertices is constructed and discussed.